Performance based assessment of reinforced concrete frames designed using eigenfrequency optimization. (2017) - Arroyo, Orlando; Liel, Abbie; Gutiérrez, Sergio
Abstract: Reinforced concrete frames (RCF) are a widely used structural system, especially in developing countries due to its economy, its capacity to withstand seismic actions and the availability of materials and construction technologies. Traditionally, these RCF buildings are designed to satisfy drift, strength and ductility requirements given by design codes. Reflecting this ubiquity, there has been a significant interest by researchers to develop efficient seismic optimization methods for RCF. Recently, an eigenfrequency optimization method has been proposed, wherein the fundamental period of RCF structures is minimized, and which has potential to be a practical tool to improve the seismic performance of this system. In this work, performance based earthquake engineering (PBEE) is used to assess the effectiveness of this optimization method for a ten story building. For this purpose, a fiber model of this building is subjected to nonlinear dynamic analyses at different seismic intensity levels, and its results are used to perform a time-based assessment to evaluate the building performance over time. The building's collapse risk, expected annual losses and the expected number of casualties are calculated. Additionally, the design characteristics of this building are investigated, including column-to-beam strength ratios and column shear and moment capacities over the height of the building. The findings show that the method produces buildings that have a more uniform drift distribution along its height, with important reductions in the bottom stories and an increase in the top stories. In addition, it reduces the buildings' susceptibility to collapse and the expected number of casualties. In terms of structural changes, it produces distributions of strength and stiffness more suitable to withstand seismic forces, specifically with stronger columns and beams, and a higher ratio of column moment strength to beam moment strength at the base of the building. All in all, results show that a design approach based on period minimization can produce important impacts on seismic design and performance by increasing stiffness – and strength – at the lower stories, particularly in columns, and distributing damage more uniformly over the height of the building.